PROSES PENGERINGAN DAN EKSTRAKSI ULTRASONIK DAUN KERSEN (MUNTINGIA CALABURA L.) SEBAGAI ANTIOKSIDAN POTENSIAL - Ayu Candraningsih; Ismiyati Ismiyati; Nurul Hidayati Fithriyah; Tri Yuni Hendrawati (Fakultas Teknik Universitas Muhammadiyah Jakarta, 2022)
Kersen (Muntingia calabura L.) is a tropical plant from the Muntingiaceae family which is a wild plant that is often found in Indonesia. This plant is one of the herbal plants that are used as natural antioxidants. The purpose of this study was to obtain a drying model of cherry leaf extract and determine the activity of flavonoids as antioxidants in cherry leaf extract. The method used to obtain cherry leaf extract using ultrasonic sonication with a wavelength of 40 kHz. Variations made in the test are the length of drying time (30 minutes, 45 minutes, 60 minutes, 90 minutes, 120 minutes) and to find the most suitable drying model between Newton and Page. Concentration of cherry leaf extract using a rotary vacuum evaporator. Identification of cherry leaf extract, namely: determining the absorbance value for flavonoids and IC50 (Inhibitor Concentration) using UV-Vis Spectrophotometry and then determining the antioxidant content. The results of the study obtained that the highest wet extract yield was treated with a drying time of 30 minutes, which was 34.1%. The highest total flavonoid content was found in the 30 minute drying time treatment, which was 51,067 g/ml. The test of antioxidant levels obtained by IC50 is 0.89 ppm which is a strong antioxidant. The most suitable drying model is the Newton drying model with the equation MR=exp-(0.0029t) with a value of R2 = 0.9867 with k = 0.0029.